Milton Romay Masciadri: narrativas (auto)biográficas sobre uma escola de contrabaixo - Lima, Diogo Baggio (2015)
The research presented by this dissertation is linked to the Research Line of Education and Arts, part of the Graduation Program in Education of the Federal University of Santa Maria, and had the main goal of comprehending the interfaces between the consolidation of a double bass school and professor Milton Romay Masciadri. In a broader view, it also has been pursued to know and spread the professor Masciadri‟s practices in the course of more than 30 years of teaching and performance with the double bass at the state of Rio Grande do Sul; to highlight some of his pedagogical and professional strategies; to contribute for the composition of the history of musical instruments teaching in Brazil; and to approximate the educational studies about teachers to the music education and instrument teaching universe. The Teacher‟s Identitary Process, theorized by NÓVOA (1992; 1995), the biographical method of FERRAROTTI (2014), and studies about conservatorial music teaching by KINGSBURY (1988), NETTL (1995), VASCONCELOS (2002) and BURWELL (2013) are significant examples of references hereby approached. The inquiry has been developed from (auto)biographical research references (NÓVOA; FINGER, 2014; BOLÍVAR, 2002; ABRAHÃO, 2004; FERRAROTTI, 2014; DOSSE, 2009) as well as from narrative inquiry studies (STAUFFER; BARRETT, 2009; CLANDININ, 2006; LOURO; TEIXEIRA; RAPÔSO, 2014), based on the Thematic Oral History methodology (MEIHY, 2005). From a scope of six semi structured interviews, the narratives of family members and ex-students of professor Masciadri had provided the necessary subsidy for an investigation about interfaces between accessions, actions and self-awareness (NÓVOA, 1992; 1995) along with the conservatorial system of double bass teaching, and the social, political and educational contexts in issue. As results we can list a deepened understanding of the intricate bonds among identitary elements of the instrument teacher‟s self, of the one-to-one pedagogy on the conservatorial music teaching, and of the hereditary consolidation of an instrument school. The conclusions that had emerged from reflections about and from narrative data point out to the contemporaneity of the educational phenomenon of musical instrument teaching, likewise to the applicability of the present assignments to the double bass teaching today.